2018
DOI: 10.3727/152599518x15346132863283
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Well-Being Potential of Participatory Arts Events for the Over 70s: A Conceptual Framework and Research Agenda

Abstract: Please check the manuscript for details of any other licences that may have been applied and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. You may not engage in further distribution of the material for any profitmaking activities or any commercial gain. You may freely distribute both the url (http://uhra.herts.ac.uk/) and the content of this paper for research or private study, educational, or not-for-profit purposes without p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Thus, this paper agrees with Arcodia and Whitford (2007), Brajša-Žganec et al (2011) and Brownett (2018) in saying that leisure activities, like festivals, promote social well-being and encourage social connections. While Wood et al (2018) argued that adults over 70s perceive a reduction of loneliness and isolation thanks to festival attendance, this paper suggests that festivals might foster social integration and, in turn, reduce loneliness for all adults over 18 years, and not just the over 70s. Festivals are arenas for people to meet, network, chat, laugh and have fun.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Thus, this paper agrees with Arcodia and Whitford (2007), Brajša-Žganec et al (2011) and Brownett (2018) in saying that leisure activities, like festivals, promote social well-being and encourage social connections. While Wood et al (2018) argued that adults over 70s perceive a reduction of loneliness and isolation thanks to festival attendance, this paper suggests that festivals might foster social integration and, in turn, reduce loneliness for all adults over 18 years, and not just the over 70s. Festivals are arenas for people to meet, network, chat, laugh and have fun.…”
Section: Discussionmentioning
confidence: 59%
“…By using the concept of social capital, Brownett (2018) also observed that arts festivals produce social well-being. Similarly, Wood et al (2018), while analysing the social benefits of art events for older adults, claimed that more studies should explore the role of events in decreasing isolation and loneliness. They also argued that, while several scholars investigated personal benefits of music festivals, more studies are needed into other forms of art, such as literature and writing.…”
Section: Festivals and Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the article by Benjamin, Knollenberg, and Chen in this issue remind us of the opportunities that lie ahead for those events operators who engage with consumers in cocreating an event experience, the articles by Kirby and Crabb, Melpignano and Azara, and Pappas are a stark reminder that, in geography, just to cite a few (Lamond & Platt, 2016;Spracklen & Lamond, 2016;Wood, Jepson, & Stadler, 2018). Those accepted articles represent a wide spectrum of research loosely falling within the "umbrella term" of Event studies (Getz, 2012), bringing in evidence of how scholars embedded within distinctive (and perhaps at a glance conflicting) disciplinary discourses can provide new innovative ways of addressing the complexities of event production and consumption encountered today (Michopoulou & Giulianno, 2018;Park & Park, 2016;Ramsbottom, Michopoulou, & Azara, 2018).…”
mentioning
confidence: 99%